The Relation of Muslim and Christian Community: Hermeneutic Contribution to Create the Third Space in the Communities - Eric D. Coblentz (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2021)
One of the social conflicts caused by the false understanding of religion often occurs, making horizontal and vertical conflicts in social life. Nevertheless, there is a way to resolve the inter-religious conflict called a ‘third space community.’ This article seeks to answer how we should interpret Jesus in two different religious communities (Islam and Christian)? With Martin Buber’s hermeneutic approach to ‘I-Thou,’ this paper describes an understanding of the “term of religions” to interpret each other in the two religious communities. Multicultural communication as a form of interpretation of the “third space” is a middle way to resolve conflicts. Thus, this paper is expected that the understanding of Jesus is not a source of division but rather a limitation of religion, culture, and horizons for its adherents. Referring to Gadamer’s concept, a one-sided understanding will prevent each society (Islam and Christian) from interpreting Jesus. Afterward, this article suggests that the understanding of Jesus let the community fully interpret it.